2013
DOI: 10.4311/2012mb0267
|View full text |Cite
|
Sign up to set email alerts
|

Sustained Anthropogenic Impact in Carter Saltpeter Cave, Carter County, Tennessee and the Potential Effects on Manganese Cycling

Abstract: Anthropogenic impact is a pervasive problem in heavily trafficked cave systems and fecal contamination is equally problematic in many cave and karst waters worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 69 publications
3
16
0
Order By: Relevance
“…Ferromanganese precipitates from Daniel Boone Caverns, a relatively pristine epigene karst cave in the Tennessee River Basin (Carmichael, Carmichael, Santelli, Strom, & Bräuer, ; Carmichael, Carmichael, Storm, et al., ), were collected in June 2014. Mn oxides form within biofilms, as coatings on rocks in pools or under seeps, as crusts along cave walls and speleothems, and as particles within mud formed by mineral weathering processes.…”
Section: Methodssupporting
confidence: 81%
“…Ferromanganese precipitates from Daniel Boone Caverns, a relatively pristine epigene karst cave in the Tennessee River Basin (Carmichael, Carmichael, Santelli, Strom, & Bräuer, ; Carmichael, Carmichael, Storm, et al., ), were collected in June 2014. Mn oxides form within biofilms, as coatings on rocks in pools or under seeps, as crusts along cave walls and speleothems, and as particles within mud formed by mineral weathering processes.…”
Section: Methodssupporting
confidence: 81%
“…In contrast, a net reduction in fungal gene copy number from 3 × 10 7 to 2 × 10 7 copies per gram of soil, wet weight was observed at the Mn Falls site between non‐manipulated and manipulated samples, corresponding with a reduction in the ratio of fungi : bacteria from 0.009 to 0.004 for Mn Falls. This finding was not unexpected, as Mn Falls was previously found to contain blooms of bacteria that produced biogenic Mn oxides as a result of exogenous carbon input in the form of untreated sewage (Carmichael et al ., ).…”
Section: Resultsmentioning
confidence: 97%
“…However, microbial manganese (II) [Mn(II)] oxidation, which produces dark brown or black cryptocrystalline material, is visible in the field and has been shown to develop in response to nutrient input in shallow epigene caves, forming a massive Mn‐oxidizing biofilm (Carmichael et al ., 2013a,b). Although input of organic acids common in sewage such as acetate, butyrate and propionate (Cummings, ) encouraged growth of a bacterially driven Mn‐oxidizing community, the input of solid litter appeared to stimulate Mn(II) oxidation primarily by fungi (Carmichael et al ., ). This suggests that simple and complex sugars (particularly in solid form) support fungally driven Mn(II) oxidation, whereas organic acids (particularly in aquatic seepage) support bacterially driven Mn(II) oxidation (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…At the time of sampling, the CSPC Mn Falls site was thought to be heavily impacted by organic input from sewage effluent (Carmichael et al 2013). Bacterial biomass in cave pools has been shown to increase proportionally with organic carbon input (Simon and Buikema Jr. 1997), and cell concentrations in the range of 1 × 10 9 cells/mL have been reported in sewage (Fierer and Lennon 2011).…”
Section: Ferromanganese Biofilm Community Compositionmentioning
confidence: 99%
“…Lechuguilla Cave has been described as deep and oligotrophic (Northup et al 2003), whereas a parallel study of CSPC indicates that it has been severely impacted by nutrient loading from the surface (Carmichael et al 2013). Future research should attempt to elucidate the cause of these observed differences, with an initial focus on the increased role of surface impact in shallow vs. deep cave systems.…”
Section: Ferromanganese Biofilm Community Compositionmentioning
confidence: 99%